Characterisation of the complete chloroplast genome of the common bean, Phaseolus vulgaris L. Issue 2 (3rd July 2018) - Meng, Xianxin; Li, Ming
Abstract: Common bean ( Phaseolus vulgaris L.) is the most important grain legume in the human diet and has a role in sustainable agriculture. In this study, we obtained the complete chloroplast genome sequence of common bean using BGISEQ-500 sequencing. Its chloroplast genome size has 155, 622 bp, containing a large single copy region (84, 924 bp), a small single copy region (18, 570 bp) and a pair of IR regions (26, 064 bp). The overall GC contents of the chloroplast genome were 37.9%. This circular genome contains 131 annotated genes, including 85 protein-coding genes, 37 tRNAs, and 8 rRNAs. The phylogenetic analysis using maximum likelihood (ML) method showed that Common bean has the closest relationship with Phaseolus coccineus L. This complete chloroplast genomes can be subsequently used for the genetic breeding and agricultural development of this valuable species.